Gender-Specific Mechanism of Synaptic Impairment and Its Prevention by GCSF in a Mouse Model of ALS - Naumenko, Nikolay; Pollari, Eveliina; Kurronen, Antti; Giniatullina, Raisa; Shakirzyanova, Anastasia; Magga, Johanna; Koistinaho, Jari; Giniatullin, Rashid (Frontiers in Cellular Neuroscience, 2011)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease of motoneurons which progresses differentially in males and females for unknown reason. Here we measured gender differences in pre- and postsynaptic parameters of the neuromuscular transmission in a mutant G93A-SOD1 mouse model of ALS. Using intracellular microelectrode technique we recorded miniature and evoked endplate potentials (MEPPs and EPPs) in the diaphragm muscle of G93A-SOD1 mice at early symptomatic stage. While no evident alterations in the amplitude of MEPPs was observed in male or female G93A-SOD1 mice, G93A-SOD1 mice displayed dramatically reduced probability of spontaneous acetylcholine release. In contrast, the EPPs evoked by single nerve stimulation had delayed latency but unchanged amplitude. In males, but not females, this was associated with reduced readily releasable transmitter pool. Transmitter release in both sexes was sensitive to the inhibitory action of reactive oxygen species (ROS), but the production of ROS was increased in the spinal cords of male but not female G93A-SOD1 mice. Treatment with granulocyte colony stimulating factor (GCSF), which we previously found to be beneficial in males, attenuated the increased ROS production indicating involvement of the antioxidant mechanisms and improved ALS-induced synaptic dysfunctions only in males being ineffective in females. Consistent with our findings at synaptic level, GCSF did not change the survival rate or motor performance of female ALS mice. In summary, neuromuscular transmission in ALS mice is impaired at early symptomatic stage when a dramatic presynaptic decline of spontaneous release associated with increased ROS production is seen in males. Beneficial effects of GCSF treatment on survival in males may be explained by GCSF-improved presynaptic functions in male G93A SOD1 mice. Development of efficient treatment strategies for ALS may need to be directed in a gender-specific manner.